Performing power : cultural hegemony, identity, and resistance in colonial Indonesia - Meer, Arnout van der, 1980- (Southeast Asia Program Publications, an imprint of Cornell University Press, 2020)
"Discusses how colonial dominance in Indonesia, and in particular on Java, was legitimized and maintained as well as negotiated and contested through the everyday staging and public performance of power between colonizer and colonized, for instance through changes in language, etiquette, deference rituals, dress, consumer patterns, and lifestyles"--